2011
DOI: 10.4314/ijbcs.v4i6.64940
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological studies of Co(II) and Cd(II) 5-(3,4,5- trimethoxybenzyl) pyrimidine-2,4-diamine (Trimethoprim) complexes

Abstract: Two metal complexes of Co(II) and Cd(II) 5-(3,4,5-trimethoxybenzyl) pyrimidine-2,4-diamine (Trimethoprim) were synthesized and characterized by both analytical and spectroscopic methods. They are 4-coordinate complex containing two molecules of 5-(3,4,5-trimethoxybenzyl) pyrimidine-2,4-diamine (TMP) and two chloride ions. A distorted tetrahedral geometry is suggested for their structure, where TMP behaves as a monodentate ligand. The metal binds through the pyrimidine N(1) of the ligand. The complexes have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…. Following the results obtained in this studies, percentage (%) reduction in parasitemia for the synthesized compounds were more potent or active as compared to similar complexes reported by Tella and Obaleye (2010) with activities less than 70% as obtained in this study.…”
Section: Antimalarial Activitysupporting
confidence: 81%
See 2 more Smart Citations
“…. Following the results obtained in this studies, percentage (%) reduction in parasitemia for the synthesized compounds were more potent or active as compared to similar complexes reported by Tella and Obaleye (2010) with activities less than 70% as obtained in this study.…”
Section: Antimalarial Activitysupporting
confidence: 81%
“…It could be a result of the coordination of the ligands to the metal ions which improve the effectiveness of the drug. It could also be observed that Co(II) and Zn(II) complexes exhibited the same antimalaria activity at 70 percent (Tella and Obaleye, 2010). The parasitemia level was determined by the number of erythrocytes that are being infected with the organisms: Plasmodium berghei.…”
Section: Antimalarial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the research work of Tella et al 12 , coordination complexes can be used as chemotherapy for the treatment of metal intoxication. Bamigboye and Ejidike 13 reported the characterization, antimalarial and antimicrobial activities of mixed ibuprofenpyrimethamine metal complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs combination improves the effectiveness of chemotherapeutic agents towards bacteria and parasite cell inhibitions 17 . It has also been sustained that combination therapy gives an effective action in bacteria resistant situation owing to previous research [10][11][12][13][14] would have an improved therapeutic action such as antibacterial and toxicological activities. The administration of the metal-drug samples to experimental animals (albino rats) was carried out in order to determine medical effect of the graded doses of the samples using biochemical parameters of the blood samples and essential organ like liver of these experimental animals.…”
Section: Introductionmentioning
confidence: 99%